Maintaining Students’ ‘Indonesian Identity’ with a Multicultural Teaching Approach - Hidayati, Kuni Hikmah (ELLITE, 2018)
Experts agree that using English as an International Language (EIL) has directlyand indirectly shaped the speakers’ ways of thinking which may finally shapetheir identity. This paper theoretically examines impacts of learning Englishtowards students’ identity, i.e. Indonesian identity. First, it explains the possibilityof Indonesian students’ changing identity as learning English in school. Then,it recommends what teachers should know about their students in order toreduce negative impacts of English to the students’ national identity. Finally,the paper purposes the notion of a multicultural teaching approach whenteaching English.